Linkages between soil respiration and soil eukaryotic microalgae following vegetation restoration in the Loess Plateau, China. (3rd March 2022) - Zhang, Lei; Lv, Junping
Abstract: Eukaryotic microalgae are widespread in soil. They are generally considered to participate in soil development and the formation of the soil food chain. Interestingly, some microalgae can grow in heterotrophic mode. Therefore, it is a reasonable speculation that eukaryotic microalgae may participate in the process of soil respiration ( Rs ) via the heterotrophic metabolism of soil organic matter. Nevertheless, the mechanism is not well understood. Here, we investigated the eukaryotic microalgal community in farmland and plantation/grassland soil via high‐throughput sequencing focusing on the Loess Plateau, China. Chlorophyta, Chrysophyta, Cryptophyta, Bacillariophyta, Dinophyta, Xanthophyta, and Haptophyta were found in all samples. Nevertheless, the biomarker for farmland soil was affiliated to Chlorophyta and Xanthophyta, whereas the biomarker for plantation/grassland soil was affiliated to Chrysophyta . Moreover, the distribution of soil microalgae was strongly dependent on soil pH, organic matter, and nitrogen. In addition, afforestation significantly decreased Rs rate, which was significantly related to the soil microalgal community, especially 11 taxa of eukaryotic microalgae affiliating to Chlorophyta and Chrysophyta . Meanwhile, the interaction between microalgae and bacteria in farmland soil was stronger than that in plantation/grassland soil, which was also likely to affect Rs rate. These results suggest that beyond plants, soil eukaryotic microalgae are functionally significant but rarely considered participants of Rs . Therefore, they should be considered when investigating soil carbon cycling.